Morphometric Indicators of The Structure of The Vascular Wall of The Liver Tissue in Diabetes Mellitus - Sobirova Dildora Ravshanovna (Genius Journals, 2023)
This article explores morphometric indicators as crucial parameters for evaluating the structural alterations in the vascular wall of liver tissue in individuals with diabetes mellitus. Diabetes mellitus is a chronic metabolic disorder that affects multiple organ systems, including the liver. The vascular wall of the liver plays a pivotal role in maintaining hepatic function and homeostasis, making its structural changes of particular significance in the context of diabetes. Through a comprehensive analysis of morphometric indicators, this study sheds light on the intricate interplay between diabetes mellitus and hepatic vascular alterations. The findings provide valuable insights into the pathophysiological mechanisms underlying liver-related complications in diabetes and may guide future therapeutic approaches.
Keywords: Morphometric indicators; Vascular wall; Liver tissues; Diabetes mellitus